DNA barcoding as a tool for early warning and monitoring alien duckweeds (Lemna sp.pl.): the case of Central Italy. (3rd September 2019) - Marconi, Gianpiero; Landucci, Flavia; Rosellini, Daniele; Venanzoni, Roberto; Albertini, Emidio
Abstract: Aquatic habitats are vulnerable to the invasion of alien species, so early warning protocols are necessary for eradication. The presence in Italy of two alien duckweeds in freshwaters has been documented: Lemna minuta, that showed high invasivity, and L. valdiviana, still confined to south Lazio. These two species may be mistaken for each other and for the domestic L. minor and L. gibba due to morphological variation. Here, we assess the applicability of DNA barcoding as a complement to morphological analysis for monitoring the spread of alien Lemna . We chose two chloroplast genome sequences for their ability to discriminate all Lemna species: the 5' intron of the trnK gene and the matK gene. Among 48 samples of Lemna collected at 20 sites in Central Italy, 20 were identified as L. minor, 19 as L. minuta, five as L. trisulca and four as L. gibba. L. minuta was present at most sampling sites; in particular, at six locations of Lake Trasimeno, eight L. minuta samples were found. We demonstrate that DNA sequence analyses with cost-effective barcoding techniques can effectively support expert efforts in species determination for an early alert system of invasive Lemna species.